The Clinicopathologic and Prognostic Significance of c-Myc Expression in Hepatocellular Carcinoma: A Meta-Analysis - Min, Zhao; Xunlei, Zhang; Haizhen, Chen; Wenjing, Zhao; Haiyan, Yu; Xiaoyun, Lu; Jianyun, Zhou; Xudong, Chen; Aiguo, Shen (Frontiers in Bioinformatics, 2021)
Background: The incidence and mortality rates of hepatocellular carcinoma (HCC) are increasing worldwide. Therefore, there is an urgent need to elucidate the molecular drivers of HCC for potential early diagnosis and individualized treatment. Whether c-Myc expression plays a role in the clinicopathology and prognosis of patients with HCC remains controversial. This meta-analysis aimed to survey the prognostic role of c-Myc in HCC. Methods: We searched the PubMed, Cochrane Library, Embase, Web of Science, and Google Scholar databases for studies published through March 2020 that examined the association between c-Myc expression and clinicopathology or prognosis in HCC patients. The pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were used to investigate the prognostic significance of c-Myc expression. Odds ratios were calculated to evaluate the association between c-Myc expression and clinicopathological features. We also tested for publication bias. Results: Our meta-analysis included nine studies with 981 patients with HCC published between 1999 and 2016. A meta-analysis of these studies demonstrated that high c-Myc expression indicated a poor overall survival (OS) (HR = 2.260, 95% CI: 1.660-3.080, P < 0.001) and disease-free survival (DFS) (HR = 1.770, 95% CI: 1.430-2.450, P < 0.001) in patients with HCC. However, high c-Myc expression was not associated with HBsAg, pathological type, TNM stage, or cirrhosis. We did not find any significant publication bias among the included studies, indicating that our estimates were robust and reliable. Conclusion: c-Myc overexpression could predict poor OS and DFS in HCC patients. c-Myc could be a useful prognostic biomarker and therapeutic target for HCC.